Exploring the Rhetoric and Reality of Performance Management Systems and Organisational Effectiveness - Evidence from Australia - Nankervis, Alan; Stanton, P.; Foley, P. (Curtin University, Singapore Human Resources Institute, 2012)
Human resource management (HRM) theorists and professionals alike have in recent decades attempted to identify the ways in which particular HRM functions (or ‘bundles’ of such functions) influence and contribute to desired overall organisational outcomes. Many have suggested that performance management, in its broadest perspective, may hold the key to such linkages. This paper draws on survey data to explore the links between performance management systems and perceived organisational effectiveness. The study canvassed the opinions of senior, line and HRM managers in a variety of organisations and industry sectors in Australia. Executives/senior managers in this study were the most supportive of a strategic approach to the PMS-organisational effectiveness relationship, followed by HR professionals, whilst middle and line managers were clearly more focused on operational and implementation perspectives. Accordingly, executives/senior managers might be characterised as the sponsors of PMS; HR professionals as their advocates; and middle and line managers as the end users of such systems and their links to organisational effectiveness.